Catholic and Feminist the Surprising History of the American Catholic Feminist Movement. - Henold, Mary J. (Chapel Hill : University of North Carolina Press, 2008)
In the first history of American Catholic feminism, Henold explores the movement from the 1960s through the early 1980s, showing that although Catholic feminists had much in common with their sisters in the larger American feminist movement, Catholic feminism was distinct and had not been simply imported from outside. Henold demonstrates that efforts to reconcile faith and feminism reveal both the complex nature of feminist consciousness and the creative potential of religious feminism.
Description based on print version record.
Keywords: Catholic women -- United States -- History -- 20th century; Feminism -- Religious aspects -- Catholic Church -- History -- 20th century; Feminism -- United States -- History -- 20th century; Women in the Catholic Church -- United States -- History -- 20th century; United States -- Church history -- 20th century; RELIGION / Christianity / Catholic; Electronic books